Logistics Risk Mitigation Strategy Using RBS and HOR Integration: Strategi Mitigasi Risiko Logistik dengan Mengintegrasikan RBS dan HOR - Sofie Amalia Afifah; Hana Catur Wahyuni (Indonesian Journal of Innovation Studies, 2025)
General Background: Logistics services play a critical role in supply chain performance, particularly in ensuring timely and accurate goods delivery. Specific Background: PT. APL faces recurring operational issues in delivery activities, including delays, damages, and discrepancies, which lead to financial losses due to customer claims. Knowledge Gap: Existing studies often apply risk analysis methods separately, leaving limited integration between structured risk identification and mitigation prioritization approaches. Aims: This study aims to identify, prioritize, and develop risk mitigation strategies in logistics service operations using an integrated Risk Breakdown Structure (RBS) and House of Risk (HOR) approach. Results: The analysis identified 18 risk events across six delivery stages caused by 29 risk agents, with the highest Aggregate Risk Potential value reaching 2,752. The study proposed four main mitigation priorities based on Effectiveness to Difficulty values, including double checking systems, checklist implementation, employee training, and operational standard setting. Novelty: This research demonstrates a structured integration of RBS and HOR to systematically connect risk identification, prioritization, and mitigation strategy development in logistics operations. Implications: The findings provide practical guidance for logistics companies in reducing operational risks and improving service quality through targeted and prioritized mitigation actions. Keywords: Logistics Risk, Risk Breakdown Structure, House of Risk, Risk Mitigation, Supply Chain Management Key Findings Highlights Identification reveals multiple delivery-stage vulnerabilities with dominant human-related causes Priority ranking isolates critical sources requiring immediate operational attention Structured actions focus on procedural control, workforce capability, and verification systems